2012
DOI: 10.4067/s0718-221x2012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Fracturas en madera de Eucalyptus nitens: efecto de las propiedades mecánicas a nivel ultraestructural y de la anatomía celular

Abstract: RESUMENSe realizó un estudio para indagar en las causas y posibles factores que originan la fractura en la estructura de la madera de Eucalyptus nitens. Para esto se examinó el comportamiento nanomecánico de la lamela media (LM), de las capas S1 y S2 de la pared celular. También se determinaron el número, área y diámetro de los vasos que están asociados a niveles de agrietamiento extremos (alto y bajo). Se estudiaron dos familias de Eucalyptus nitens procedentes de dos sitios de la 8 va Región de Chile. Median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
1
4
0
2
Order By: Relevance
“…However, the influence of vessels frequency and diameter on the parameter area of vessels per area of interest varies according to the studied material. For example, Gacitúa et al (2007) found higher area of vessels per area of interest in the material that showed higher vessels frequency, whereas Valenzuela et al (2012) observed higher area of vessels per area of interest in the material with higher vessels diameter.…”
Section: Relations Between Anatomy and Behavior Of Woods Subjected Tomentioning
confidence: 95%
See 1 more Smart Citation
“…However, the influence of vessels frequency and diameter on the parameter area of vessels per area of interest varies according to the studied material. For example, Gacitúa et al (2007) found higher area of vessels per area of interest in the material that showed higher vessels frequency, whereas Valenzuela et al (2012) observed higher area of vessels per area of interest in the material with higher vessels diameter.…”
Section: Relations Between Anatomy and Behavior Of Woods Subjected Tomentioning
confidence: 95%
“…The vessels diameter was lower in the juvenile wood than in the mature wood, but showed a higher end check score (C2), indicating an inverse relation. Gacitúa et al (2007) and Valenzuela et al (2012) analyzed the occurrence of check in E. nitens wood aged 16 and 12 years, respectively, and stated that the area of vessels per area of interest is directly related to the occurrence of check in wood. This phenomenon is attributed to the higher concentration of stresses generated around the vessels in the materials with larger area of vessels per area of interest, leading to tissue rupture.…”
Section: Relations Between Anatomy and Behavior Of Woods Subjected Tomentioning
confidence: 99%
“…Lo contrario sucede con la capa S 2 que es más dúctil, lo que le permite soportar mayores deformaciones asociadas a las tensiones de crecimiento. La diferencia en E/H entre la capa S 2 y la LM generaría esfuerzos de corte que provocarían la separación y formación de microgrietas (Valenzuela et al 2012a). Putoczki et al (2007), argumentan que cuando dos capas constituidas por materiales distintos son sometidas a cierta carga, solo una de ellas podrá deformarse elásticamente sin fracturarse dada la diferencia de ductilidad entre ellas.…”
Section: Resultados Y Análisisunclassified
“…Un método no destructivo para obtener estas propiedades nanomecánicas es la técnica de nanoindentación. Esta técnica ha sido utilizada para investigar el comportamiento de la madera o composite (Wu et al 2009, Muñoz et al 2012, Valenzuela et al 2012a, Konnerth y Gindl 2006, Bustos et al 2011. Otra característica que puede ser considerada para segregar árboles Eucalyptus nitens es la frecuencia de grietas debido a que se presentan de acuerdo a las características del árbol (Valenzuela 2012b, Leandro et al 2008).…”
Section: Introductionunclassified
“…They observed that the average area of the vessel was higher in the samples with visible checks than in the samples without visible checks. Valenzuela et al (2012a) analyzed the checks and characteristics of the vessels in 12-year-old E. nitens wood samples and found a higher vessels diameter and higher average area of vessels in the wood with a higher percentage of checks. Soares et al (2019), studying the juvenile wood and the mature wood of E. cloeziana at the age of 37 years, stated that the lower vessel frequency and higher vessel diameter found in mature wood were associated with a lower occurrence of end checks.…”
Section: Introductionmentioning
confidence: 99%